Regional therapy in metastatic melanoma: an update on minimally invasive intraarterial isolated limb infusion and percutaneous hepatic perfusion. (October 2014) - Rashid, Omar M; Sloot, Sarah; Zager, Jonathan S
Abstract : Introduction: The management of locoregioanlly metastatic melanoma of the limb and metastatic melanoma to the liver poses a clinical challenge with limited therapeutic options. An effective therapeutic modality includes regional intraarterial perfusion-based therapy. Percutaneous vascular isolation as in isolated limb infusion (ILI) and percutaneous hepatic perfusion (PHP) provide the additional advantage of minimally invasive techniques to further limit morbidity. Areas covered: This review includes the technical aspects of ILI, PHP, the chemotherapeutic agents used and clinical responses. Also reviewed are pharmacokinetics and novel methods to enhance delivery of chemotherapeutics for both ILI and PHP and the efforts to improve therapeutic response and limit toxicity. Expert opinion: Metastatic melanoma, particularly unresectable disease in the liver and in-transit disease in the limb, poses a clinical challenge with few effective treatments available. Although systemic therapy with immunotherapy or targeted therapy is an option, these modalities are associated with some systemic toxicity. Modalities that target treatment regionally, particularly minimally invasive techniques such as ILI and PHP, provide promising options to focus therapy on treating the affected limb or liver. The effectiveness of these minimally invasive methods has been supported by retrospective studies as well as prospective trials.